Pengembangan Computer Assisted Instructional Integrated Science Materi “Hujan” di Sekolah Dasar - Setria Utama Rizal; Din Azwar Uswatun; Astri Sutisnawati; Rifki Aditia (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2020)
The lack of learning media is one indicator of science learning less favored by elementary school students. The use of instructional media can overcome students' difficulties in understanding contextually material. The purpose of this research is to produce integrated learning media Computer Assisted Instructional learning material